Microstructure, mechanical properties and cutting performance of superhard (Ti,Si,Al)N nanocomposite films grown by d.c. reactive magnetron sputtering - Carvalho, S. (2004)
This paper reports on the optimization of coating properties to improve the performance of tools in severe cutting conditions. Tungsten carbide tools coated with (Ti,Si,Al)N films deposited by d.c. reactive magnetron sputtering have been investigated. The structure and the hardness of the coated samples were analyzed by X-ray diffraction (XRD) and depth-sensing indentation, respectively. XRD results revealed a structure indexed to fcc TiN. The tool life and tool failure modes were examined for various cutting conditions. A promising wear performance of the (Ti,Si,Al)N coatings was confirmed by scanning electron microscopy observations complemented with energy dispersive X-ray spectrometry analysis. At higher cutting speed (200 m/min) it seems that after turning 15 min the cutting performance of (Ti,Si,Al)N coated tools is better than that presented by the commercial multilayer coating (TiCN/Al2O3/TiN)--which was used as a reference. Also regarding the final surface finish of the steel workpiece, the (Ti,Si,Al)N coatings outperformed the commercial tool, considering that the roughness of the workpiece is smaller in the former case (4 [mu]m) than that measured in the latter one (12 [mu]m).